CAREER QUEST: MEDIA PERMAINAN INTERAKTIF DALAM PERENCANAAN CAREER SISWA SMAN 5 KOTA SERANG - Galuh Mulyawan; Siti Aisyah Saragih; Rida Nurfallah; Sukma Damayanti; Dila Shiva Sabilla (Jurnal Pendidikan Sultan Agung, 2025)
Career planning is a very crucial part of a teenager's life, especially in high school. At this stage, students face various choices that will affect their future, such as academic majors, job sectors, and personal development. However, many of them do not yet have a deep understanding of their abilities and the work environment they will enter. To overcome this deficiency, learning innovations have emerged through interactive game media, one of which is Career Quest. The purpose of this study is to help students find their interests in career choices through the career quest game method, so that students can better understand and feel interested that career planning is very important for their future. Based on data from students who took Career Quest, it is known that the financial aspect of students reached 33.6%, the level of student satisfaction or happiness was at 55.5%, and social acceptance of students obtained results of 10.9% of the total students of class XI IPS 4. In this study, the approach applied was qualitative. This research is descriptive qualitative, the process of which includes planning, implementation, observation, and reflection. The case study method was chosen to explore a deep understanding of the individual as a whole and comprehensively. This step aims to understand the character of the individual who is the subject of the research in depth.